Social representations as a framework for understanding human responses in nursing care - Vanesa Jiménez Arroyo; Yesica Yolanda Rangel Flores (Universidad de Alicante, 2018)
Human responses are complex and are based on how relevant social, cultural, economic and political micro, meso and macro in which people operate contexts conditions. The nurse needs an epistemological, philosophical and methodological perspective that allows him to understand the ways in which people are positioned against health-disease processes depend not only on a personal decision but a posture collectively built. The aim is to reflect on the contributions made by the theory of social representations (RS) to understanding the complexity of human responses to human care. For the construction of the document the contributions of classic authors to the theory of RS, these contributions reflect from the experiences of health care were recovered. It identifies possible that this theoretical framework to explain the complexity and variability of human responses of people facing processes of health and disease, and social and historical contexts in which subjects and develop their social group.